1995
DOI: 10.1111/j.1432-1033.1995.0270l.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of Arginine Residues for the Activity of Fasciculin

Abstract: The West African green mamba, Dendroaspis angusticeps, has two toxins, fasciculins, that are noncompetitive inhibitors of acetylcholinesterase. Arginine residues of fasciculin 2 were modified with 1,2-cyclohexanedione. Two of these residues, Arg24 and Arg37, reacted very slowly or not at all. Modification of Arg28 reduced the activity only by 13%. Argll and Arg27 are unique for fasciculins; a comparison of the sequences of 175 snake toxins homologous to fasciculins showed that no other toxin has arginine in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…Karlsson and coworkers neutralized positive charges on Fas by chemical modification of single lysines or arginines, and reported a substantial decrease in Fas activity (Cervenansky et al ., 1994; Cervenansky et al ., 1995). Marchot et al .…”
Section: Introductionmentioning
confidence: 99%
“…Karlsson and coworkers neutralized positive charges on Fas by chemical modification of single lysines or arginines, and reported a substantial decrease in Fas activity (Cervenansky et al ., 1994; Cervenansky et al ., 1995). Marchot et al .…”
Section: Introductionmentioning
confidence: 99%
“…The fact that the 3D structure of AChE [12] became available at about the same time as that of FAS-I [8] stimulated a wave of experimental studies aimed at elucidating the molecular basis for inhibition, using conventional enzyme kinetics [27][28][29], as well as chemical modification [25,30,31] and site-directed mutagenesis [29,32]. A theoretical study, in which docking of FAS onto the AChE structure was attempted, has also been published [33].…”
Section: Introductionmentioning
confidence: 99%
“…A theoretical study, in which docking of FAS onto the AChE structure was attempted, has also been published [33]. Chemical modification suggested participation of a number of conserved basic residues of FAS in the interaction with AChE [25,30], and further suggested that the interaction took place at the peripheral anionic site of AChE, which is located at the mouth of the active-site gorge [31]. Site-directed mutagenesis has provided evidence for participation of aromatic residues from the peripheral site of mouse AChE (Tyr70, Tyrl21 and Trp279) in the interaction with FAS [32].…”
Section: Introductionmentioning
confidence: 99%
“…These structures are generally very similar, revealing that Fas binds to a peripheral anionic site of AChE, thus sealing a gorge that leads to the active site. Fas inhibits h AChE with K i of 10 −11 M . This extraordinarily high affinity has been attributed to a remarkable surface complimentarity between the two proteins, as well as to a considerable burial of the hydrophobic surface area upon binding .…”
Section: Introductionmentioning
confidence: 99%